A REVIEW OF CONSUMER PAYMENT BEHAVIOUR ON DIGITAL PLATFORM: A PRISMA METHOD - Ahmad Nordin, Atiqah Hanim; Ismail, Nurazleena (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2025)
Rising in smartphone usage and improved internet access have fuelled the global expansion of digital payment systems. This paper examines how consumer make payments in the dynamic fintech industry while providing a methodical summary of important concepts, theoretical underpinnings, and publishing patterns. Using PRISMA guidelines, a systematic literature review (SLR) was carried out with an emphasis on empirical research on consumer payment behaviour. Excluded were studies from unrelated fields including blockchain, marketing, and health technology. Dominant theoretical frameworks, such as the Unified Theory of Acceptance and Use of Technology (UTAUT) and the Technology Acceptance Model (TAM), were discovered by classifying journals according to quartile rankings. Results show that past research has increased significantly since 2021, with a focus on youth and general consumers. With an emphasis on concepts including perceived ease of use, trust, financial literacy, and social influence, TAM and UTAUT were the models that were used the most. When trust-based models and innovation diffusion theory are combined, potential avenues for improving the robustness of current frameworks are revealed. This study emphasizes the need for more studies to examine underrepresented populations, such as older users and educators, and to evaluate regional differences in the uptake of digital payments. For academics, practitioners, and policymakers seeking to promote inclusive and efficient digital payment ecosystems, this study provides insightful information by charting the theoretical and demographic outlines of consumer payment behaviour research.